Synthesis of strontium tetroborate SrB₄O₇ for single crystal growth - Korshikova, T.I.; Parkhomenko, S.V.; Tolmachev, A.V.; Yavetskiy, R.P. (Functional Materials, 2007)
The possiblility of the single phase SrB₄O₇ synthesis the amorphous phase formation stage has been shown. Using XPA and DTA methods, the formation of strontium borate hydrates has been determined to occur at T = 95±5°C in the course of strontium carbonate interaction with boric acid. The dehydration of strontium borate crystal hydrates results in amorphous phase formation. A further phase transition (borate rearrangement) of this phase at T = 750°C results in formation of polycrystalline SrB₄O₇.